Efficiency at Maximum Power in a Parallel Connected Two Quantum Dots Heat Engine - Tibebe Birhanu; Yigermal Bassie; Yoseph Abebe; Mulugeta Bekele (Journal of Engineering)
In this paper, we proposed a model in which a single level of two quantum dots is connected in parallel and embedded between two leads with different temperatures and chemical potentials. The temperature and chemical potential gradient help the electron flow cyclically and act as a heat engine. We explore the thermodynamic properties of the model such as heat flux and power as a function of dot energy. We also carried out analytical and numerical solutions for efficiency at maximum power of the thermoelectric engine. The resulting efficiency of our engine agrees with the Curzon–Ahlborn expression up to quadratic terms in Carnot efficiency.